2005
DOI: 10.1104/pp.105.060079
|View full text |Cite
|
Sign up to set email alerts
|

Genome Organization of More Than 300 Defensin-Like Genes in Arabidopsis  

Abstract: Defensins represent an ancient and diverse set of small, cysteine-rich, antimicrobial peptides in mammals, insects, and plants. According to published accounts, most species' genomes contain 15 to 50 defensins. Starting with a set of largely nodulespecific defensin-like sequences (DEFLs) from the model legume Medicago truncatula, we built motif models to search the nearcomplete Arabidopsis (Arabidopsis thaliana) genome. We identified 317 DEFLs, yet 80% were unannotated at The Arabidopsis Information Resource a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
234
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(255 citation statements)
references
References 69 publications
9
234
0
4
Order By: Relevance
“…One of the most used methods for AMP discovery is the analysis of homologs of known genes by comparing new sequences with sequences of biochemically characterized AMPs Pestana-Calsa and Calsa Jr. 2011), since the sequence segments with high identity tend to share structure and function. For example: an in silico search based on HMMs (Silverstein et al 2005) supported genome assignment of 317 defensin-like sequences in Arabidopsis thaliana; a novel cathelicidin-like AMP, designated cathelicidin-AM, was identified (Yan et al 2011) by mining the genome of panda using BLAST and the sequence of a dog cathelicidin; and the systematic mining of the Nasonia vitripennis genome (Tian et al 2010), using the tools BLASTP, translated BLAST nucleotide (TBLASTN) and ScanProsite (http://prosite.expasy.org/scanprosite/scanprosite-doc. html), has delivered a large and diverse peptidome AMP repertoire of defensins, abaecins, hymenoptaecins and tachystatins.…”
Section: Genomicsmentioning
confidence: 99%
“…One of the most used methods for AMP discovery is the analysis of homologs of known genes by comparing new sequences with sequences of biochemically characterized AMPs Pestana-Calsa and Calsa Jr. 2011), since the sequence segments with high identity tend to share structure and function. For example: an in silico search based on HMMs (Silverstein et al 2005) supported genome assignment of 317 defensin-like sequences in Arabidopsis thaliana; a novel cathelicidin-like AMP, designated cathelicidin-AM, was identified (Yan et al 2011) by mining the genome of panda using BLAST and the sequence of a dog cathelicidin; and the systematic mining of the Nasonia vitripennis genome (Tian et al 2010), using the tools BLASTP, translated BLAST nucleotide (TBLASTN) and ScanProsite (http://prosite.expasy.org/scanprosite/scanprosite-doc. html), has delivered a large and diverse peptidome AMP repertoire of defensins, abaecins, hymenoptaecins and tachystatins.…”
Section: Genomicsmentioning
confidence: 99%
“…2 and 3), such interactions have to be studied on a case-by-case basis for a purposeful plant genotype selection, as pointed out for the diamondback moth in oilseed rape (Sarfraz et al, 2006(Sarfraz et al, , 2007. Promising biochemical traits other than glucosinolates have been pointed out by Silverstein and co-authors regarding defensins and smaller cysteine-rich peptides for the establishment of constitutive resistance against insect pests (Silverstein et al, 2005(Silverstein et al, , 2007. Trait selections in less important species, e.g.…”
Section: Includementioning
confidence: 99%
“…Like defensins, the CCPs could be characterized by a conserved signal peptide, a highly divergent mature peptide with the exception of conserved Cys residues, and tissuespecific expression. Using CCP motif models developed from M. truncatula and soybean, Silverstein et al (2005) identified .300 defensin-like genes in the Arabidopsis genome. Genome analyses revealed that plant defensins had many features of classical R genes including clustering and evolution by duplication and positive selection.…”
Section: Analysis Of Ests Identifies Genes Involved In Nodulation Andmentioning
confidence: 99%
“…Silverstein et al (2005) Using the same approach, we identified M. truncatula and soybean cDNA contigs that were statistically overrepresented (P , 0.05) with ESTs from at least two different pathogen or rhizobia-inoculated libraries. Of the 4,588 contigs identified from soybean, 65% were specific to defense, 27% were specific to nodulation, and 8% were expressed during nodulation and defense.…”
Section: Analysis Of Ests Identifies Genes Involved In Nodulation Andmentioning
confidence: 99%